Enhancing STEM learning through extracurricular activities: Insights from Japanese students - Rashed, Nagwa Fekri (American Journal of STEM Education, 2024)
I examine the impact of STEM extracurricular activities at Japanese Colleges of Technology (KOSENs) through qualitative analysis of semi-structured interviews with twelve prize-winning students from a private KOSEN. The research explores how these activities foster confidence, curiosity, and interest in STEM careers, promoting scientific inquiry through open-ended research experiences. Students value the autonomy to choose research topics, finding individual projects more engaging and enriching than group work or traditional coursework. The findings underscore the importance of extracurricular research in enhancing both academic and personal development, offering real-world applications of STEM education. The study highlights KOSEN’s role in nurturing critical thinking and independent learning, contributing to student growth and future career readiness.